Total Net Energy Assessment for Rule-of-Thumb Applications in Multicomponent Distillation Separation Strategy - Istadi, Istadi; Riyanto, Teguh (UPT Laboratorium Terpadu, Universitas Diponegoro, 2025)
Energy saving in separation systems, particularly in distillation systems, is a research field that has attracted considerable innovative approaches. A distillation system is an essential separation process, yet it is inefficient in using thermal energy, and may operate with adverse environmental impact as it discharges a large amount of thermal energy into the environment. In this work, several Sequences Designs of Distillation Column Network are proposed to be compared with respect to Total Net Energy of each sequence design. Applying the Rule of Thumb of Distillation Strategy for separating multicomponent mixtures is important by performing the easiest separation first (largest relative volatility), that is, the one least demanding of trays and reflux, and leaving the most difficult to the last. From all sequence designs results, Sequence-A shows the lowest Total Net Energy (9,750,720.88 kJ/h), because the Sequence-A follows the strategy/procedure for separation of multicomponent using distillation column network. Decreasing the relative volatility affects on increasing number of tray and recycle ratio required for distillation process and decreasing the Net Energy. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).